2008
DOI: 10.1177/1536867x0800800203
|View full text |Cite
|
Sign up to set email alerts
|

SNP and SML Estimation of Univariate and Bivariate Binary-Choice Models

Abstract: We discuss the semi-nonparametric approach of Gallant and Nychka (1987, Econometrica 55: 363-390), the semiparametric maximum likelihood approach of Klein and Spady (1993, Econometrica 61: 387-421), and a set of new Stata commands for semiparametric estimation of three binary-choice models. The first is a univariate model, while the second and the third are bivariate models without and with sample selection, respectively. The proposed estimators are √ n consistent and asymptotically normal for the model parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 20 publications
0
56
0
1
Order By: Relevance
“…By relaxing assumptions on the joint distribution of e and v, such that the form of FðÁ; ÁÞ is unknown, the approximation methodology from Stewart (2004) and De Luca (2008) can be generalized to deal with the case here. This is the semiparametric estimation of De Luca and Perotti (2011).…”
Section: Model Specification Estimation and Test: Sample Selectionmentioning
confidence: 99%
“…By relaxing assumptions on the joint distribution of e and v, such that the form of FðÁ; ÁÞ is unknown, the approximation methodology from Stewart (2004) and De Luca (2008) can be generalized to deal with the case here. This is the semiparametric estimation of De Luca and Perotti (2011).…”
Section: Model Specification Estimation and Test: Sample Selectionmentioning
confidence: 99%
“…While originally it was used in research areas other than agricultural economics, it is now quickly entering this field as well. Recent "agriculture-oriented" studies that use this approach include Hess and von Cramon-Taubadel (2007, 2008, Gallet (2007Gallet ( , 2010, Johnston and Duke (2009) and Lagerkvist and Hess (2011).…”
Section: Empirical Approachmentioning
confidence: 99%
“…The latter have the advantage of not requiring the true parametric model to be specified by the researcher. However, while theoretically possible, 26 the intercept is typically not identified in these models, and so this approach is not suitable for estimating population means based on binary outcomes, such as HIV prevalence. Semi-parametric approaches that allow for the estimation of the intercept require additional assumptions and have only been developed for the case of continuous outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the true distribution of the error terms is not bivariate normal, then the estimates are likely to be both inconsistent and inefficient. 26 Simulation studies have indicated that HIV prevalence estimates from selection models may indeed be sensitive to violations of this assumption. 27 …”
mentioning
confidence: 99%